Analisa Kinerja Apache dan Nginx dalam Arsitektur Microservice Menggunakan Siege - Howard Christopher Yoel Unsong; Justinus Andjarwirawan (Jurnal Infra, 2021)
From the existing problem, there is how to make sure that an API with an internal network will not slow down the response time overall and how to use load balancer results without scalability. This thesis aims to solve this problem by analyzing the performance of the web service on the microservice architecture between apache and nginx by using siege on IP version 4. The method used is qualitative, which distinguishes it from other studies, this study uses a microservice architecture and uses siege as a tool to run scenarios that are tested. The result is that the apache web server works better than the nginx web server in response time and throughput, but the nginx web server hits transactions more than apache . The conclusion is in accordance with the emphasis in the problem formulation, so that the performance of the apache web server is better.